Baumol's Diseases: The Case of Switzerland - Jochen Hartwig (Swiss Journal of Economics and Statistics, 2010)
Nordhaus (2008) has developed a testing strategy for what he calls "Baumol's diseases", by which name he designates a number of by-products of structural change that are unwanted from an economic policy perspective. He finds that the U.S. economy is strongly affected by the "diseases". This paper applies Nordhaus's testing methodology to Swiss data. The results suggest that – unlike the U.S. – Switzerland is not affected by the most serious of the "diseases", namely the negative impact of structural change on economic growth.
Keywords: C12; C23; O41; O47; O52; 330; Baumol's disease; productivity growth; Switzerland